Is the Anatomical Type of the Arcus Aorta an Effective Factor for the Success of Endovascular Therapy? - Murat Çabalar; Nihat Şengeze; Alper Eren; Yusuf İnanç; Semih Giray (Cam & Sakura Medical Journal, 2021)
Objective: This study aimed to investigate the relationship between the aortic arch structure classification and the success of endovascular reperfusion therapy in acute ischemic stroke (AIS). Material and Methods: Between January 2018 and December 2018, 207 patients, who were brought to the Stroke Center of Gaziantep University, Şahinbey Research and Practice Hospital due to AIS and who underwent endovascular therapy, were analyzed retrospectively. The demographic features of patients, aortic arch classification, and modified-thrombolysis-in-cerebral-infarction (mTICI) scores used for reperfusion in endovascular therapy were evaluated. Findings were statistically analyzed (p<0.05). Results: A total of 207 patients underwent endovascular procedures with the mean age was 64.4+-13 years, wherein 69 (33.3%) had type 1 aortic arch, 99 (47.8%) had type 2 aortic arch, and 39 (18.8%) patients had type 3 aortic arch, whereas 47 (22.7%) patients had a bovine arch. TICI 2b and above recanalization were achieved in 188 (90.8%) patients after endovascular therapy. At the end of the third month, good clinical outcomes were observed as modified Rankin scale of 0-2 in 78 (37.7%) patients, whereas 61 (29.5%) patients had mortality. The prognosis was worse in patients with type 3 aortic arch structure (p=0.016). Conclusion: Our study revealed that complex aortic arch structure had no negative effect on the success of endovascular therapy. However, the prognosis was poor at the end of the third month in patients with complex aortic arch structures.